Structural, Optical, Antibacterial and Anticancer Properties Silver Barium Modified Titanium Dioxide Nanoparticles Prepared via a Green Process Using Withania somnifera Hairy Roots - Palusamy, Raja; Ganesan, Thiagu; Shajahan, Appakan; Chandrasekaran, Thilip; Sangilimuthu, Alagar Yadav; Umaralikhan, Liyahathalikhan (Asian Journal of Biological and Life Sciences)
Aims: The current study sought to assess the antibacterial and anticancer properties of AgBamodified TiO2 nanoparticles produced by a green method using a hairy root extract from Withania somnifera. Materials and Methods: The synthesized samples were examined through X-ray Diffraction (XRD) investigations, SEM and Energy-Dispersive X-ray analysis (EDX), Dynamic Light Scattering (DLS), Fourier Transform Infrared (FTIR) Spectroscopy, Ultraviolet (UV) Spectroscopy, and Photoluminescence (PL) spectra. Results: SEM validated the produced nanoparticle’s sphericallike shapes with EDX analysis, which confirmed the crystallite size of 70 nm as determined by DLS. In addition, oxygen vacancies in synthesized nanoparticles were found between 501 and 521 nm in the PL spectra. Conclusion: The primary focus of this study is on the environmentally friendly plant-based synthesis of biomedically important AgBa-modified TiO2 using aqueous Withania somnifera hairy root, and it has the potential antibacterial against S. aureus, S. pneumoniae, B. subtilis, K. pneumoniae, E. coli, P. vulgaris and anticancer activity against blood cancer cell lines (MOLT-4).
Keywords: AgBa modified TiO2; Antibacterial; Anticancer activity; Green process; Withania somnifera hairy roots